Cancer-associated fibroblast-like fibroblasts in vocal fold leukoplakia suppress CD8+T cell functions by inducing IL-6 autocrine loop and interacting with Th17 cells. (10th October 2022) - Fang, Yi; Chen, Min; Li, Guangfei; Yang, Yue; He, Peijie; Chen, Jian; Cheng, Lei; Wu, Haitao
Abstract: The characteristics of fibroblast cells in head and neck precancerous lesion and its ability to secrete inflammatory cytokines and affect CD8 + T cell functions remain unclear. Herein, we reported the existence of fibroblasts in human-derived vocal fold leukoplakia (VFL) with positive staining of fibroblast activation protein (FAP) and α-smooth muscle actin (α-SMA). The fibroblasts from VFL and cancer-associated fibroblasts (CAFs) from head and neck squamous cell carcinoma (HNSCC) displayed similar cellular functions and robust inflammatory cytokine secretions. The effects of fibroblasts from VFL in inducing the apoptosis, depletion of CD8 + T cells and recruitment of regulatory T cells (Treg cells) were observed. We further assessed the autocrine loop within VFL fibroblasts to self-stimulate by secreting IL-6, TGF-β through the IL-6/JAK2/STAT3 pathway. The synergistic stimulation of IL-6 and TGF-β promoted Th17 cell differentiation and IL-17A secretion, which could result in fibroblast activation in another positive loop. Tocilizumab (TOC), a monoclonal antibody targeting IL-6R, managed to suppress the overexpression of both IL-6 and TGF-β in VFL fibroblasts, and thus blocking IL-6 autocrine loop and CAF-Th17 loop in vitro. In a murine model of oral leukoplakia (OL), local injection of TOC inhibited the outgrowth of lesions and showed notable effect in control of OL progression in vivo. Our findings establish a novel rationale for blocking the IL-6/JAK2/STAT3 pathway to inhibit vocal fold (oral) leukoplakia progression and postpone HNSCC tumorigenesis. Highlights: Identification of fibroblasts in vocal fold leukoplakia similar with cancer-associated fibroblasts. Fibroblasts in leukoplakia induce CD8 + T cell apoptosis and exhaustion, and Treg recruitment via IL-6/JAK2/STAT3 pathway. Fibroblasts of vocal fold leukoplakia perform self-stimulation of IL-6/JAK2/STAT3 loop and interacting with Th17 cells. Tocilizumab can suppress fibroblasts of leukoplakia in vitro and reverse the precancerous lesion progression in vivo.